Acceptance, Behavioral Intention, and Usage among Clients of a Government Office on Mobile Payment Services - Lagunday, Eriz Jireh B.; Menes, Carmen C. (Philippine Social Science Journal, 2025)
Focused on a government office in rural Southern Negros, this descriptive-correlational study analyzed the acceptance, behavioral intention, and usage of Mobile Payment Services (MPS) among individual taxpayers and business entities. Results from self-administered questionnaires revealed high overall acceptance and intention—driven largely by performance expectancy—yet a significant disparity emerged in actual usage, with individuals consistently outperforming businesses. While statistical analysis confirmed that acceptance strongly predicts usage, the gap between business sentiment and practice highlights a critical opportunity for government offices to drive financial inclusion through targeted support systems. Consequently, the study recommends specific strategies to address business client concerns, with future research directed toward qualitative investigation of adoption barriers and longitudinal tracking of intervention effectiveness.